Conservation of plant genes : DNA banking and in vitro biotechnology - Adams, Robert P.; Adams, Janice E. (Academic Press, 1992)
This is the first report of the DNA Bank-Net, an organization whose goal is to encourage the conservation, collection, and preservation of plant genes. DNA banking and gene retrieval Oligonucleotides from endangered/extinct species Operation of a DNA banking facility The impact of intellectual property rights in developing countries Interim preservation of plants for DNA use Cryopreservation of fruit stocks Critical review of international conservation efforts.